Intervensi pemerintah di sektor kesehatan: regulasi monopoli-oligopoli = Government intervention in the health sector: monopoly-oligopoly regulation - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Monopoly refers to an industry in which there is one supplier of a good, service, or resource that has no close substitutes, and in which there is a barrier preventing the entry of new firms. Monopoly causes welfare loss, since it produces output level lower than competitive one, and sets price exceeding the competitive price, hence it causes: (1) Pareto-suboptimality of reÂ¬source allocation